2007
DOI: 10.1209/0295-5075/79/48001
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary design of functional networks robust against noise

Abstract: PACS 89.75.Hc -Networks and genealogical trees PACS 89.20.-a -Interdisciplinary applications of physics PACS 89.75.Fb -Structures and organization in complex systems Abstract -Robustness against noise is characteristic for biological networks of a living cell. Engineering of artificial noise-robust networks is important for various industrial and logistic applications. Here, flow distribution (pipeline) networks, representing a simplification of biological signal transduction systems or a toy model of logistic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
17
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 18 publications
0
17
0
Order By: Relevance
“…It has been shown that, by using evolutionary optimization methods, functional networks, that generate definite output patterns, can be designed [7]. Moreover, networks with high robustness against deletion of links or nodes and introduction of quenched noise have been obtained; statistical analysis of the properties of the designed networks has been performed [8,9]. Additionally, networks which generate programmable time-dependent responses have also been considered [10].…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that, by using evolutionary optimization methods, functional networks, that generate definite output patterns, can be designed [7]. Moreover, networks with high robustness against deletion of links or nodes and introduction of quenched noise have been obtained; statistical analysis of the properties of the designed networks has been performed [8,9]. Additionally, networks which generate programmable time-dependent responses have also been considered [10].…”
Section: Introductionmentioning
confidence: 99%
“…The constructive approach for studies of bionetworks has been followed in our recent publications [6][7][8]. Using a simplified model representing an abstraction of biological signal processing, ensembles of networks with the same output functions have been generated, which were additionally designed to be self-correcting against deletion of individual links or nodes, or against the application of distributed quenched noise.…”
mentioning
confidence: 99%
“…This kind of optimization, Metropolislike methods, have been used in the construction of genetic networks [13][14][15][16], and, flow processing networks [17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%